Salivary progesterone and cervical length measurement as predictors of spontaneous preterm birth. (July 2015) - Maged, Ahmed M.; Mohesen, Mohamed; Elhalwagy, Ahmed; Abdelhafiz, Ali
Abstract Objective: To evaluate the efficacy of salivary progesterone, cervical length measurement in predicting preterm birth (PTB). Methods: Prospective observational study included 240 pregnant women with gestational age (GA) 26–34 weeks classified into two equal groups; group one are high risk for PTB (those with symptoms of uterine contractions or history of one or more spontaneous preterm delivery or second trimester abortion) and group 2 are controls. Results: There was a highly significant difference between the two study groups regarding GA at delivery (31.3 ± 3.75 in high risk versus 38.5 ± 1.3 in control), cervical length measured by transvaginal ultrasound (24.7 ± 8.6 in high risk versus 40.1 ± 4.67 in control) and salivary progesterone level (728.9 ± 222.3 in high risk versus 1099.9 ± 189.4 in control; p < 0.001). There was a statistically significant difference between levels of salivary progesterone at different GA among the high risk group (p value 0.035) but not in low risk group (p value 0.492). CL measurement showed a sensitivity of 71.5% with 100% specificity, 100% PPV, 69.97% NPV and accuracy of 83%, while salivary progesterone showed a sensitivity of 84% with 90% specificity, 89.8% PPV, 85.9% NPV and accuracy of 92.2%. Conclusion: The measurement of both salivary progesterone and cervical length are good predictors for development of PTB.